ANALYSIS OF THE PERFORMANCE OF HAJJ UMRAH EXECUTORS DURING THE COVID-19 PANDEMIC PT.GADIKA TRAVEL MEDAN - Yurik, Wanti; Edi, Sarwo (TALENTA Publisher, Universitas Sumatera Utara, 2023)
This research was conducted with the aim of analyzing the travel performance of the performance of Hajj and Umrah at PT.Gadika Travel Medan. This reseach was obtained by the formance of the executor of travel that the performance of Hajj and Umrah could improve the walfare of the pligrims. This reseach method uses qualitative research with the type of case study reseach. Data collection tecniques used in this study were observation, interviews and documentation. Based on the result of reseach and analysis of key data that with the performance of this Umrah pilgrimage can improve the welfare of the Umrah pligrims at PT.Gadika Travel Medan.